Improving Teacher Competence in Questions on Google Forms Through In House Training (IHT) in the Era of the COVID-19 Pandemic at Candirejo State Elementary School, Kalibawang, Kulon Progo Regency - Paryati Paryati (Universitas Islam Indonesia, 2021)
The purpose of this study is to improve the ability of teachers in preparing questions on google forms. Building teachers' practical ways of thinking in solving problems related to the preparation of HOTS questions, as well as increasing the professionalism of school principals in organizing In House Training (IHT) and increasing the motivation and competence of school principals during the COVID-19 pandemic. This research method is descriptive qualitative through school action research which further deepens the teacher development process related to writing HOTS questions on the google form. The data of this study are qualitative data, while the research subjects are Candirejo State Elementary School teachers, totaling 8 teachers consisting of 6 classroom teachers and 2 study teachers. The results showed that the teacher's ability to write written test questions was initially only 2 people (20%), after the research was carried out with the first cycle of activities from 2 teachers to 8 teachers (100%), while the research activities at the end the implementation of the second cycle of activities with an average score of 69.00 and an average score of 3.80, while based on presentation it reached 94.91%. As for the stage of the second cycle of meeting 1 the teacher's ability in preparing questions through In House Training (IHT) on Google Form there was an increase of 2.14% and at the second meeting of cycle II it rose to 91.79% in the